Approximation of classes of periodic multivariable functions by linear positive operators - Bushev, D. M.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
In an N-dimensional space, we consider the approximation of classes of translation-invariant periodic functions by a linear operator whose kernel is the product of two kernels one of which is positive. We establish that the least upper bound of this approximation does not exceed the sum of properly chosen least upper bounds in m-and ((N ? m))-dimensional spaces. We also consider the cases where the inequality obtained turns into the equality.